2021
DOI: 10.1371/journal.pone.0247370
|View full text |Cite
|
Sign up to set email alerts
|

Can late stage marine mortality explain observed shifts in age structure of Chinook salmon?

Abstract: Chinook salmon (Oncorhynchus tshawytscha) populations have experienced widespread declines in abundance and abrupt shifts toward younger and smaller adults returning to spawn in rivers. The causal agents underpinning these shifts are largely unknown. Here we investigate the potential role of late-stage marine mortality, defined as occurring after the first winter at sea, in driving this species’ changing age structure. Simulations using a stage-based life cycle model that included additional mortality during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The total return of tagged adults to the river Bush (3) in comparison to the potential return to the coast (5-9 fish) implies potential losses of between 40% and 66% from the available returning cohort during the final 45 km of open ocean migration. Recent work on Pacific salmon has also indicated that late-stage marine mortality, defined as mortality after the first winter at sea, was higher than had previously been assumed (Manishin et al, 2021) and, alongside the present work, highlights the need for more focus on the sources of late-stage mortality. In the current study, late-stage marine losses may be linked to predation.…”
supporting
confidence: 68%
“…The total return of tagged adults to the river Bush (3) in comparison to the potential return to the coast (5-9 fish) implies potential losses of between 40% and 66% from the available returning cohort during the final 45 km of open ocean migration. Recent work on Pacific salmon has also indicated that late-stage marine mortality, defined as mortality after the first winter at sea, was higher than had previously been assumed (Manishin et al, 2021) and, alongside the present work, highlights the need for more focus on the sources of late-stage mortality. In the current study, late-stage marine losses may be linked to predation.…”
supporting
confidence: 68%
“…Furthermore, our analysis focused on potential bottom-up effects on the size-at-age of Chinook salmon and did not account for possible top-down mechanisms (e.g. Ohlberger et al 2019;Manishin et al 2021). Because of these limitations, it is important to consider our findings in the context of prior work on the topic and other forms of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, age 6 fish are rarely observed today, and most fish return to spawn at age 3 (Satterthwaite et al 2017). Shifts in the age structure of Chinook salmon are likely due to a combination of factors, including fisheries, warming environmental conditions, marine predation, competition, and hatchery practices (Barnett et al 2017;Chasco et al 2017;Ohlberger et al 2018Ohlberger et al , 2019Seitz et al 2019;Oke et al 2020;Manishin et al 2021;Munsch et al 2022).…”
Section: Introductionmentioning
confidence: 99%